Utility of ultrasonography for prediction of difficult airway and assessment of dynamic airway changes - Shehla Bashir; Suhail Sidiq; Bashir Ahmad Dar; Majid Jehangir; Razia Hamid; Feroze Shaheen; Abdul Waheed Mir (Asian Journal of Medical Sciences, 2024)
Background: Several clinical tools are used for preoperative airway assessment. Ultrasound is an emerging tool in anesthesia, and its role in the upper airway needs to be explored. Aims and Objectives: We aimed to assess the role of airway ultrasound in predicting difficult laryngoscopy and airway changes following induction of anesthesia. Materials and Methods: Clinical airway assessment was performed with a modified Mallampati score in 100 elective surgical patients. Ultrasound variables in pre- and post-induction of anesthesia were: distance between the skin and vocal cords at the hyoid bone (DSVC hb), distance from the skin to the thyroid isthmus, distance from the skin to the tracheal ring at suprasternal notch level, and distance between the skin and the cricothyroid (DSCM). Cormack–Lehane (CL) grades 3b and 4 were classified as having a DL. Association of clinical, ultrasonography (USG) indicators and CL grading was correlated. Dynamic changes in anterior neck tissues following induction of anesthesia were also measured. Results: Pre-induction USG variables were significantly higher in the DL group compared to the NDL group (P<0.05), except DSCM. Post-induction all USG parameters were significantly higher in the DL group. Among USG variables, DSVC hb and DTSI had the highest AUCs of 0.801 and 0.772, respectively. DSVC hb had a sensitivity of 76% and a specificity of 100% for DL. DTSI had a sensitivity of 92% and a specificity of 72%. There was a significant increase in depth after anesthetic induction of all USG parameters except DSCM. Conclusions: Ultrasound of anterior airway tissues can be considered for prediction of DL and allows dynamic airway assessment.